Advancing Sexual and Reproductive Health and Rights in Africa Constraints and Opportunities - Durojaye, Ebenezer; Mirugi-Mukundi, Gladys; Ngwena, Charles (Routledge Contemporary Africa, 2021)
This book explores recent developments, constraints and opportunities relating to the advancement of sexual and reproductive health and rights in Africa. Despite many positive developments in relation to sexual and reproductive health in recent years, many Africans still encounter challenges, for instance in poor maternity services, living with HIV, and discrimination on the basis of age, gender, sexual orientation or identity. Covering topics such as abortion, gender identity, adolescent sexuality and homosexuality, the chapters in this book discuss the impact of culture, morality and social beliefs on the enjoyment of sexual and reproductive health and rights across the continent, particularly in relation to vulnerable and marginalized groups. The book also explores the role of litigation, national human rights institutions and regional human rights bodies in advancing the realization of sexual and reproductive health and rights in the region. Throughout, the contributions highlight the relevance of a rights-based framework in addressing topical and contentious issues on sexual and reproductive health and rights within Sub-Saharan Africa. This book will be of interest to researchers of sexuality, civil rights and health in Africa.